The effect of breakfast energy, physical endurance, and speed on physical education learning achievement - Randa Andayana; Alnedral Alnedral; Wilda Welis; Anton Komaini (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aims to reveal the direct and indirect effects, as well as the simultaneous effects between variables. This is a quantitative associative study using a path analysis approach. The population in this study was all 612 Physical Education (PJOK) students at SMAN 5 Batam. A sample of 123 students was taken using purposive sampling. Data were collected using a questionnaire for breakfast energy, a bleep test for physical endurance, a 30-meter run test for speed, and report card scores for learning achievement. The data were analyzed using path analysis through a structural model test at α = 0.05. The results of the hypothesis testing show: (1) there is a direct effect of breakfast energy on PJOK learning achievement (py1 = 0.435 or 18.92%), (2) there is a direct effect of physical endurance on PJOK learning achievement (py2 = 0.564 or 31.08%), (3) there is a direct effect of speed on PJOK learning achievement (py3 = 0.057 or 0.27%), (4) there is an indirect effect of breakfast energy on PJOK learning achievement (p31.py3 = 0.886 or 78.49%), (5) there is an indirect effect of physical endurance on PJOK learning achievement (p32.py3 = 0.0345 total effect 3.49%), and (6) there is a simultaneous effect of breakfast energy, physical endurance and speed on PJOK learning achievement (Rsquare = 0.886 or 88.6%).